Magnetic Nanoparticle Mediated Steroid Delivery Mitigates Cisplatin Induced Hearing Loss - Ramaswamy, Bharath; Roy, Soumen; Apolo, Andrea B.; Shapiro, Benjamin; Depireux, Didier A. (Frontiers in Cellular Neuroscience, 2017)
Cisplatin (cis-diamminedichloroplatinum) is widely used as a chemotherapeutic drug for genitourinary, breast, lung and head and neck cancers. Though effective in inducing apoptosis in cancer cells, cisplatin treatment causes severe hearing loss among patients. Steroids have been shown to mitigate cisplatininduced hearing loss. However, steroids can interfere with the anti-cancer properties of cisplatin if administered systemically, or are rapidly cleared from the middle and inner ear and hence lack effectiveness when administered intra-tympanically. In this work, we deliver prednisolone-loaded nanoparticles magnetically to the cochlea of cisplatin-treated mice. This magnetic delivery method substantially reduced hearing loss in treated animals at high frequency compared to control animals or animals that received intratympanic methylprednisolone. The method also protected the outer hair cells from cisplatin-mediated ototoxicity.